Heavy metal removal using activated carbon from bamboo for underground water treatment - Mohamad Hanif, Rashidi Ragunathan (2025)
Heavy metal pollution of underground water is a global issue that has emerged as a major challenge for scientists, environmentalists, and even policymakers. As a result of excessive heavy metal exposure from tainted drinking water, which affects millions of people worldwide, heavy metal poisoning has now emerged as one of the biggest environmental concerns in the world. To put safety measures and controls in place, it is important to understand the health risk that heavy metal in underground water poses. The objective of this study was to analyze heavy metal contaminations which are arsenic, lead and copper in underground water samples from Kota Bharu, Kelantan and evaluate the efficacy and optimal amount of Bamboo-Activated Carbon in removal heavy metal from underground water. The study uses Inductively Coupled Plasma Mass Spectrometry (ICP-MS) to evaluate the efficacy of Bamboo-Activated Carbon at various concentrations. The results show that a 50g dosage achieves optimal performance, lowering arsenic from 3.52 ppb to 2.36 ppb, copper from 8.63 ppb to 5.42 ppb, and lead from 6.21 ppb to 3.87 ppb. These quantities are far below the limits established by Malaysia's National Drinking Water Quality Standards, guaranteeing that the treated water fulfils safe consumption standards. This study emphasises the importance of the activation process in improving the adsorption properties of Bamboo-Activated Carbon, specifically its microporous and mesoporous structures, which allow for efficient heavy metal uptake. The findings also highlight the material's cost-effectiveness and environmental benefits, as bamboo is a widely available and renewable resource in Malaysia. While the findings show great promise, the study also suggests areas for future research, including as optimising activation procedures, analysing the adsorption of additional pollutants, and investigating the regeneration capacity of BAC for reuse. Overall, this study demonstrates the viability and sustainability of bamboo-derived activated carbon as a solution for enhancing water quality and preserving public health. The study emphasises the importance of the activation phase in increasing adsorption efficiency and the necessity for further optimisation and investigation of regeneration approaches.